2011
DOI: 10.1111/j.1466-7657.2011.00951.x
|View full text |Cite
|
Sign up to set email alerts
|

Saudi Arabian nurses' experiences of studying Masters degrees in Australia

Abstract: Highly skilled local nursing professionals are being sought in many Middle Eastern countries and may undertake post-graduate studies in Western contexts quite different from their own. Students reported that, in spite of difficulties, their experience prompted transformational change: intellectually, psychologically and developmentally. It is necessary for staff to understand expectations and learning preferences of these students to ensure fruitful learning outcomes and benefits to nursing in their home count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…These challenges are similar to studies conducted nationally and internationally such as the studies by Clerehan et al (2012), Shen (2008) and Essa (2011). Despite no real differences were noticed between part-time and full-time students in this study (except on employment challenges), various programmes challenges should be explored by academic staff and support should be provided.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…These challenges are similar to studies conducted nationally and internationally such as the studies by Clerehan et al (2012), Shen (2008) and Essa (2011). Despite no real differences were noticed between part-time and full-time students in this study (except on employment challenges), various programmes challenges should be explored by academic staff and support should be provided.…”
Section: Resultssupporting
confidence: 80%
“…Similarly, Essa (2011) and Clerehan et al (2012) found that many postgraduate students felt that the lecturers were distant, inaccessible, unapproachable and abrupt and this seemed to be the case whether the students stayed in the same or a different province than where the institution was situated. Frischer and Larsson (2000) and Wadesango and Machingambi (2011) concur with the importance of support by explaining that the supervisorsupervisee relationship is central to progress and completion.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Nursing education in KSA is evolving. While nursing in the region has not been traditionally viewed as a highly respected profession, over time, more Saudi nationals have been entering the nursing profession 3 . High school students are encouraged to pursue nursing, as their tuition and books are free, and students are given a stipend to attend government university nursing programmes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is little or no emphasis put on the development of communication, critical-thinking, and analytic skills. As a result, Saudi students seeking medical education in Western-styled universities have to rapidly 1) adapt to a different language of instruction and 2) modify their learning habits (7). Students spending one full year in such preparatory programs are expected to perform very well.…”
Section: Medical Education In Saudi Arabiamentioning
confidence: 99%